Feminist foreign and development policy in practice: Requirements and potentials - Claudia Zilla (Stiftung Wissenschaft und Politik (SWP), 2024)
Feminist foreign policy (FFP) provides a policy framework for government action and for processes and structures within ministries. The introduction of such a framework is linked to a change in policy that is intended to help reduce discriminatory asymmetric relations of power. FFP is a new political concept that has emerged in the context of increasing gender awareness in international politics. The Swedish government was the first to officially describe its foreign policy as feminist in 2014. Other countries from various regions have gradually followed suit. Germany joined the trend in March 2023, when the Federal Foreign Office published its guidelines for feminist foreign policy and the Federal Ministry for Economic Cooperation and Development published its strategy for a feminist development policy. Both ministries see their documents as unfinished concepts that - with the help of research - will be adapted and further developed. This study, with its 11 application-oriented analyses, can contribute towards this effort. In addition to the core elements of national FFP concepts, German and European policy towards selected countries (states in Eastern Europe as well as Turkey, the Palestinian territories and Iran) as well as individual policy areas and international instruments (trade policy, digital policy, migration, flight and displacement, stabilisation and sanctions) are examined with regard to the limits and potentials of implementing FFP.
Keywords: 320; feminist foreign and development policy; feminist foreign policy (FFP); discriminatory asymmetric relations of power; gender awareness; Federal Foreign Office; Federal Ministry for Economic Cooperation and Development; Russia; Turkey; Palestinian territories; Iran; trade policy; digital policy; migration; flight and displacement; stabilisation; sanctions; Convention on the Elimination of All Forms of Discrimination against Women (CEDAW); "Women; Peace and Security" (WPS)